A Journal of the Plague Year: Rapid-Response Archiving Meets the Pandemic. Issue 3 (September 2021) - Tebeau, Mark
Pandemics challenge the foundations of social life, pushing us apart even as we yearn for human contact. A Journal of the Plague Year: An Archive of COVID-19 (JOTPY) emerged as effort by historians and archivists to document the current crisis. Rapid-response archival projects and two decades of digital archiving work, have provided the framework driving the development of JOTPY's mission, including (among other things) a commitment to addressing the silences in traditional archives, collecting ethically, and developing robust metadata—a particular strength of JOTPY. Nonetheless, archiving pandemic nonetheless presents a distinctive problem that has suggested an altogether new type of rapid-response archive. More broadly, JOTPY is part of a global effort to document the pandemic and seeks to provide a useful model for other research teams involved in this important work.